Ekspansi Gerakan Islam Transnasional di Indonesia - Faizal Arifin (Jurnal Iman dan Spiritualitas, 2021)
This book provides a kind of strategic recommendation or sharing of strategies and organized efforts, namely for Islamic organizations, institutions and communities in the form of 12 recommendation points to avoid infiltration and "attacks" from various hard-line groups. That is an invitation to continue learning, stop and break the spread of hard-line understanding, raise awareness the elites, realizing Pancasila that reflects Sharia for all beings. In collaboration with NU clerics with the understanding of Ahlussunnah wal Jama'ah, in collaboration with scholars, intellectuals, culturalists, educational practitioners, entrepreneurs, creating clean, fair and law-abiding government institutions, fostering understanding and awareness of the noble values of Islam, building a network of the Red-White love movement, as well as growing confidence and pride that the traditions and culture of the nation itself are in line with the religious teachings of the Indonesian people.